OPTIMIZATION OF ORTHOPEDIC TREATMENT OF DENTAL DEFECTS IN PATIENTS WITH CHRONIC GASTROINTESTINAL DISEASES - Sadriev Nizom Nazhmiddinovich (Journals Park Publishing, 2022)
Prosthetics for defects in teeth and dentition is one of the most important links in specialized medical care for the population. Prosthetics - not only eliminates the aesthetic defect, restores the impaired function of the dentition, but also serves as an important way to prevent diseases of the gastrointestinal tract.
Keywords: general pathology of the gastrointestinal tract, orthopedic constructions, apoptosis